Testing the Reproducibility of the Effects of Transcranial Direct Current Stimulation: Failure to Modulate Beauty Perception by Brain Stimulation - Takahashi, Kuri; Yotsumoto, Yuko (Frontiers in Human Neuroscience, 2022)
Transcranial direct current stimulation (tDCS) has been recognized as a promising tool for investigating the causal relationship between specific brain areas of interest and behavior. However, the reproducibility of previous tDCS studies is often questioned because of failures in replication. This study focused on the effects of tDCS on one cognitive domain: beauty perception. To date, the modulation of beauty perception by tDCS has been shown in two studies: Cattaneo et al. (2014) and Nakamura and Kawabata (2015). Here, we aimed at replicating their studies and investigating the effects of tDCS on beauty perception using the following parameters: (1) cathodal stimulation over the medial prefrontal cortex (mPFC) (Nakamura and Kawabata, 2015); (2) anodal stimulation over the left dorsolateral prefrontal cortex (lDLPFC) (Cattaneo et al., 2014). We also performed a more focal stimulation targeting the orbitofrontal cortex (OFC) to determine the optimal stimulation site for modulating beauty perception (3). Participants rated the subjectively-perceived beauty of the images before and after the tDCS administration. We divided images into four clusters according to the obtained scores in our preliminary study and examined changes in beauty ratings in each image cluster separately to exclude factors, such as stimuli attributions that may reduce tDCS effects. The results showed no strong effects of tDCS with the same parameters as in previous studies on beauty rating scores in any image cluster. Likewise, anodal stimulation over the OFC did not result in a change in rating scores. In contrast to previous studies, the current study did not corroborate the effects of tDCS on beauty perception. Our findings provide evidence regarding the recent reproducibility issue of tDCS effects and suggest the possible inflation of its effects on cognitive domains.